Experimental modal analysis procedure for a laser spot welded hat-plate structure - Mohamad Syazwan, Mohd Zin; M. N., Abdul Rani; M. A., Yunus; W. I. I., Wan Iskandar Mirza; M. S. M., Sani (IOP Publishing, 2019)
Measuring the dynamic behaviour of a structure made from light thin steel sheets becomes arduous as a result of the double impact, local modes and mass loading issues which lead to inaccurate results. In addition, the attachments of accelerometers, selection of suspension types and methods of excitation adopted to the measurement greatly affect the quality of the experimental results. The aim of this paper is to present detailed procedure for the experimental setup of a welded structure made from thin steel sheets. A hat shaped plate and flat plate connected together by several laser spot welds were used for the demonstration of the experimental modal analysis. The laser spot welded hat-plate structure was tested under free-free boundary conditions using impact testing with roving accelerometers and an LMS Test Lab. This work revealed that the proper procedures used for the experimental setup would help dynamicists enhance and improve the quality of the measured results of frequency response function and the results could be confidently used for the validation purposes and updating analytical models.